1. ## solve

I have a problem that I am in need of assistance with.

Here it goes...

7y-2(y-7)=11y-(7y+10)

I think I solve it like this

7y(y-7)=7y^2+49
2(y-7)= 2y+14

then move the minus sign to inside of the parentheses so the other side will look like so.

11y-7y-10

my problem then looks like this
7y^2+45-2y = 11y-7y-10

then combine like terms
7y^2+45-2y=4y-10

is this correct??

2. Originally Posted by planolerachel
I have a problem that I am in need of assistance with.

Here it goes...

7y-2(y-7)=11y-(7y+10)

I think I solve it like this

7y(y-7)=7y^2+49
2(y-7)= 2y+14

then move the minus sign to inside of the parentheses so the other side will look like so.

11y-7y-10

my problem then looks like this
7y^2+45-2y = 11y-7y-10

then combine like terms
7y^2+45-2y=4y-10

is this correct??

$7y-2(y-7)=11y-(7y+10)$

expand the brackets gives

$7y-2y+14=11y-7y-10$

simplify each side

$5y+14=4y-10$

group y terms on one side and constant terms on the other

$5y-4y=-10-14$

and finally

$y=-28$

3. ## thank you

I knew I wasn't doing something right.. I appreciate your help.

4. Originally Posted by planolerachel
I knew I wasn't doing something right.. I appreciate your help.

I appreciate the thanks!